Towards an enhanced pipeline health monitoring system - FBG temperature and strain sensor - Sim, Noel Katrina Yi Ting (2016)
Fiber optic sensors usage for structural sensing and monitoring has increased over the years. The potential use of FBGs for simultaneous monitoring of temperature and strain for assessment of gas pipeline health proved to be desirable. With the benefits of its immunity to electromagnetic interference, multiplexing capabilities and ease of installation over conventional sensors, it provides a cost effective and safe approach for distributed and localized sensing for early detection of cracks and leakage. The objective of this project is to simultaneously monitor temperature and strain of FBG for early detection of anomalies like leakage, cracks and excavation. This report focuses on the characterization of strain and temperature sensitivity of the FBG and its surface strain changes induced by internal gas pressure change. It reviews on the distributed temperature sensing for pipeline leakage and its linear demodulation method for error compensation of temperature and strain FBG. Results demonstrate that commercially package FBGs prove to be more effective and ideal than in-house FBGs in the monitoring of temperature and strain simultaneously. Future work can include data mining integrated with all parameters of acoustic emission, temperature, strain and pressure to provide a real life simulation on gas pipeline. Design and development of system analytics reporting and data visualization can be explored to provide a more robust system sensing network to detect early stage gas leakage, crack and excavation.